EFFECT OF AGE AND LONGITUDINAL STEM SECTION OF LEGI BAMBOO (Gigantochloa atter (Hassk.) Kurz) AS FURNITURE AND HANDICRAFT MATERIALS - Rini - Pujiarti (Wood Research Journal, 2022)
Legi bamboo (Gigantochloa atter (Hassk.) Kurz) is a common and commercially important bamboo species for furniture and craft material. The aims of this research were to investigate the optimum processing quality for the furniture and craft material of 3 and 4 years old Legi bamboo in each stem section including processing properties and supporting information such as physical, mechanical, as well as adhesion properties. The result showed that optimal processing properties of Legi bamboo had average sawing defect of 1.93% (very good); drilling defect of 26.68% (good); planning defect of 4.70% (very good); lathing defect of 7.95% (very good), and sanding defect of 2.14% (very good), considered as I – II class of processing.  The results of this study indicate that the tip section of 3 years old Legi bamboo had the best physical, mechanical, and processing properties for its utilizations.